fo024131: Stockholm 1917
"Zwart-witfoto van Duitse meerderheidssocialisten te Stockholm.V.l.n.r. : F. Ebert, Eduard David, Philipp Scheidemann, Herman Müller, Richard Fischer, Herman Molkenbuhr en Johann Sassenbach, 1917. FULL TEXT AVAILABLE AT AMSAB-ISH"